Animal models of T-cell acute lymphoblastic leukemia: mimicking the human disease - Qin You, BS; Hexiu Su, BS; Jingchao Wang, MS; Jue Jiang, MS; Guoliang Qing, PhD; Hudan Liu, PhD (Journal of Bio-X Research, 2018)
Abstract. T-cell acute lymphoblastic leukemia (T-ALL) is a heterogeneous group of hematological tumors composed of distinct subtypes that vary in their genetic abnormalities. In the past decade, large-scale genomic analysis has shed new light on providing potentially important oncogenic or tumor suppressive candidates involved in the disease progression. Following in silico analysis, functional studies are usually performed to vigorously investigate the biological roles of candidate genes. For this purpose, animal models faithfully recapitulating the human disease are widely applied to decipher the mechanism underlying T-cell transformation. Conversely, an increased understanding of T-ALL biology, including identification of oncogene NOTCH1, TAL1 and MYC as well as tumor suppressor phosphatase and tensin homolog (PTEN), has significantly improved the development of T-ALL animal models. These progresses have opened opportunities for development of new therapeutic strategy to benefit T-ALL patients. In this review, we particularly summarize the mouse and zebrafish models used in T-ALL research and also the most recent advances from these in vivo studies.